Functional characterisation of dyslexia-susceptibility candidate genes KIAA0319 and KIAA0319L - Guidi, L (2017)
The capacity for language is one of the key features underlying human cognition and evolution. However, little is known about the neurobiological mechanisms underlying normal or impaired linguistic ability. Developmental dyslexia refers to a specific impairment in reading performance and it is one of the most common neurodevelopmental disabilities in school-aged children. It has a well-established genetic component and KIAA0319 is one of the prime susceptibility candidate genes associated with it, also showing some genetic overlap with other language-related disorders. Its paralogous gene, KIAA0319L (or KIAA0319-Like), is the only other member of this gene family and has also been linked to dyslexia. This thesis interrogates the function of the mouse homologs of KIAA0319 and KIAA0319L at the molecular, cellular, electrophysiological and behavioural levels in order to uncover the mechanisms through which they may underlie the neural architecture of language, and susceptibility to dyslexia and related disorders. Both KIAA0319 and KIAA0319L have been implicated in neuronal migration in the developing neocortex following in utero knockdown in rats using shRNA. However, our laboratories have recently shown that genetic ablation of KIAA0319 does not affect cortical migration. Given functional redundancy between paralogous genes is a well-known source of compensation in biological systems, I hypothesised that this may derive from compensation between KIAA0319 and AU040320, the mouse homolog of KIAA0319L. Using a range of anatomical methods to investigate AU040320 and double Kiaa0319;AU040320 KOs, I have found no evidence for a role of these proteins in cell migration in the mouse brain, in contrast to previous reports. To interrogate other putative functions of KIAA0319 and AU040320, I performed a series of behavioural experiments on Kiaa0319;AU040320 KO mice to examine potential deficits in their behaviour. Despite a largely normal behavioural profile, these animals displayed impaired auditory processing in a gap detection task and in auditory brainstem recordings (ABRs) due to a potential reduction in neural activity in the early central auditory pathway - with similar deficits observed in AU040320 single KOs. These results raise the possibility these genes mediate the normal structure/function of the auditory system, in line with auditory-related deficits being one of the hallmarks of dyslexia. Given the paucity of knowledge on the AU040320 protein, I interrogate its function at the cellular level by examining the male infertility observed in AU040320 KO mice. Spermatozoa in these mice were found to have round heads lacking the sperm secretory organelle called acrosome, features which mimic those of globozoospermia - a rare genetic condition affecting humans. Ultrastructural analyses revealed that acrosome formation in AU040320-deficient males resulted from an impairment in the fusion of proacrosomic vesicles during the early stages. Preliminary molecular analyses revealed that the AU040320 protein may interact with AP-1, AP-2 and ASAP1, key proteins in intracellular trafficking which regulate vesicle transport and function, suggesting a pathway which could be involved in the malformations observed in AU040320 KOs.